2019
DOI: 10.1021/acs.biochem.9b00659
|View full text |Cite
|
Sign up to set email alerts
|

Arg-513 and Leu-531 Are Key Residues Governing Time-Dependent Inhibition of Cyclooxygenase-2 by Aspirin and Celebrex

Abstract: Aspirin and Celebrex are well-known timedependent inhibitors of the cyclooxygenases (COX). Molecular dynamics simulations suggest that Arg-513 and Leu-531 contribute to the structural mechanisms of COX inhibition. We used mutagenesis and functional analyses to characterize how substitutions at these positions influence time-dependent inhibition by aspirin and Celebrex. We show that substitutions of Leu-531 with asparagine and phenylalanine significantly attenuate time-dependent inhibition of COX-2 by these dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Its implication in cancer has been associated with COX inhibition via acetylation of the active site, where AA binds. This accounts for COX-1 isozyme inhibition, while in COX-2, aspirin binding produces a structural rearrangement shifting the cyclooxygenase towards the lipoxygenase activity [86,87]. Therefore, AA oxygenation and cyclization to form a 15R-Prostaglandin endoperoxide is promoted, which favors the production of Prostaglandin D 2 (PGD 2 ) (with has a suggested function in inflammation resolution) instead of PGE 2 [88].…”
Section: Loxsmentioning
confidence: 99%
“…Its implication in cancer has been associated with COX inhibition via acetylation of the active site, where AA binds. This accounts for COX-1 isozyme inhibition, while in COX-2, aspirin binding produces a structural rearrangement shifting the cyclooxygenase towards the lipoxygenase activity [86,87]. Therefore, AA oxygenation and cyclization to form a 15R-Prostaglandin endoperoxide is promoted, which favors the production of Prostaglandin D 2 (PGD 2 ) (with has a suggested function in inflammation resolution) instead of PGE 2 [88].…”
Section: Loxsmentioning
confidence: 99%
“… 136 However, the presence of the extra methyl group in threonine as opposed to serine must influence the substrate’s conformation in such a way as to result in a change in the orientation of oxygen addition at carbon-15. Furthermore, the presence of the larger side chain of Thr-530 is predicted to alter the binding pose of AA in such a way as to require movement of Leu-531 in order to accommodate the C-terminal end of the substrate, as was observed in the crystal structure of a complex of V349I COX-2 with AA 56 (see Section 4.1.2 ). To test this hypothesis, the effects of L531F and L531N mutations on products formed following aspirin acetylation were explored.…”
Section: Interactions Of Cox Proteins With Inhibitorsmentioning
confidence: 99%
“…In an attempt to explain the change in stereochemistry observed with the Ser-530 COX-2 mutant enzymes, which is also observed upon aspirin acetylation of COX-2 (see Section 5.2.10 ), a 2.2 Å resolution crystal structure of V349I COX-2 in complex with Co 3+ -protoporphyrin IX and AA (PDB 6OFY) was obtained. 56 This enzyme was selected due to its production of mostly 15( R )-HETE and 15( R )-PGH 2 as products. 47 The findings revealed that AA is bound in an inverted, unproductive conformation in one subunit and a productive conformation in the second.…”
Section: Interactions Of Cox Proteins With Fatty Acidsmentioning
confidence: 99%
See 2 more Smart Citations